Analyzing relationships among success variables of construction partnering using structural equation modeling: a case study of Taiwan’s construction industry - Chen, Wei Tong; Chen, Tung-Tsan; Lu, Chun Sheng; Liu, Shu-Shun (Journal of Civil Engineering and Management, 2012)
This study explored the success variables (SVs) in construction partnering and the relationships among the SVs using structural equation modeling (SEM). Research results show that four successful factors (collaborative team culture, long-term quality perspective, consistent objectives, and resource sharing) have a significant influence on the success of construction partnering. Of the four factors, collaborative team culture and consistent objectives have the highest correlation. Collaborative team culture and long-term quality perspective have the lowest correlation. Additionally, good cultural fit has the most influence on characterizing collaborative team culture, commitment to continuous improvement has the highest influence in characterizing long-term quality perspective, clear understanding has the highest influence in characterizing consistent objectives, and availability of resource has the highest influence in characterizing resource sharing. The proposed SEM framework provides information which enables the users to control individual SV by considering their relationships with other SVs.